Potensi Zakat Maal dalam Mensejahterakan Masyarakat Miskin (Studi Kasus Baznas Padang Lawas) - Samsul Anwar Nasution; Junda Harahap; Nur Jannah Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The potential of zakat maal in Islamic economics is that zakat is a fiscal instrument in economic practice that has been used since the Prophet Muhammad SAW, and based on historical records zakat has played a very important role in the income distribution mechanism in the economy. This can be realized if the potential of zakat can truly be explored effectively and efficiently. The potential of zakat maal in improving the welfare of the poor at BAZNAS Padang Lawas is that the potential for zakat increases by 5% - 10% every year. However, looking at the potential for zakat in Padang Lawas Regency and the realization of zakat, infaq and alms collection carried out by BAZNAS, it can be said that its management has reached a fairly good optimal level.